The impact of low-skilled immigration on female labour supply - Emanuele Forlani; Elisabetta Lodigiani; Concetta Mendolicchio (Institut für Arbeitsmarkt- und Berufsforschung (IAB), 2013)
This paper contributes to the literature on the impact of immigrants on native female labour supply. By segmenting the market by educational levels, we are able to investigate which native-born women are more affected by an increase of low-skilled immigrants working in the household service sector. We present a model of individual choice with home production and, using an harmonized dataset (CNEF), we test its main predictions. Our sample includes countries implementing different family policies. Our results suggest that the share of immigrants working in services in a given local labour market is positively associated with the probability of native-born women to increase their labour supply at the intensive margin (number of hours worked per week), if skilled, and at the extensive margin (participation decision), if unskilled. Moreover, they show that these effects are larger in countries with less family-supportive policies. – – Wir untersuchen die Auswirkungen von Zuwanderung auf das Arbeitsangebot einheimischer Frauen. Insbesondere betrachten wir die Auswirkung des Anstiegs geringqualifizierter Zuwanderer, die im Haushaltssektor arbeiten, auf hoch- und geringqualifizierte einheimische Frauen. Wir modellieren individuelle Entscheidungen über die Haushaltsproduktion und testen die wichtigsten Aussagen dieses Modells anhand eines harmonisierten Datensatzes (CNEF). Unsere Stichprobe enthält Länder mit unterschiedlich großzügiger Familienpolitik. Unsere Ergebnisse zeigen, dass mit einem höheren Anteil an Migranten im Dienstleistungssektor eines lokal begrenzten Arbeitsmarktes die einheimischen hochqualifizierten Frauen ihr Arbeitsangebot erhöhen. Gleichzeitig steigt die Partizipationsrate unqualifizierter einheimischer Frauen. Darüber hinaus zeigen wir, dass diese Effekte in Ländern mit restriktiverer Familienpolitik stärker ausfallen.
Keywords: J22; J61; 330; Female labour participation; international migration; family policy